PENGEMBANGAN E-MODUL PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN STEM UNTUK MENINGKATKAN KEMAMPUAN SPASIAL SISWA - Dian Fatma Diva; Nur Rahmi Rizqi; Jihan Hidayah Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by students’ low spatial ability in learning geometry, especially on polyhedra topics, and the continued use of conventional modules that lack interactive and engaging features. To address these issues, this study aims to develop a STEM-based (Science, Technology, Engineering, and Mathematics) mathematics e-module to improve students’ spatial ability. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with a descriptive approach. The subjects were tenth-grade students at SMAS Al Washliyah Pasar Senen Medan in the 2024/2025 academic year. Expert validation results showed that the developed e-module was highly valid, with an average score of 84.25%. The practicality level was high, as rated by teachers and students, with a score of 77.3% (practical category). Regarding effectiveness, classical mastery reached 88.1%, and students’ average spatial ability scores increased from 90.5 (small group trial) to 91.25 (field trial). The e-module effectively supported students’ understanding of spatial concepts through interactive and contextual digital learning.This study concludes that the STEM-based mathematics e-module developed is valid, practical, and effective for enhancing students’ spatial abilities. The product serves as a promising digital learning resource for 21st-century mathematics education.